The effect of IPC on central and peripheral fatiguing mechanisms in humans following maximal single limb isokinetic exercise. Issue 8 (25th April 2019) - Halley, Samuel L.; Marshall, Paul; Siegler, Jason C.
Abstract: Ischemic preconditioning (IPC) has been suggested to preserve neural drive during fatiguing dynamic exercise, however, it remains unclear as to whether this may be the consequence of IPC‐enhanced muscle oxygenation. We hypothesized that the IPC‐enhanced muscle oxygenation during a dynamic exercise task would subsequently attenuate exercise‐induced reductions in voluntary activation. Ten resistance trained males completed three 3 min maximal all‐out tests (AOTs) via 135 isokinetic leg extensions preceded by treatments of IPC (3 × 5 min bilateral leg occlusions at 220 mmHg), SHAM (3 × 5 min at 20 mmHg) or CON (30 min passive rest). Femoral nerve stimulation was utilized to assess voluntary activation and potentiated twitch torque during maximal voluntary contractions (MVCs) performed at baseline (BL), prior to the AOT (Pre), and then 10 sec post (Post). Tissue oxygenation (via near‐infrared spectroscopy) and sEMG activity was measured throughout the AOT. MVC and twitch torque levels declined (MVC: −87 ± 23 Nm, 95% CI = −67 to −107 Nm; P < 0.001, twitch: −30 ± 13 Nm; 95% CI = −25 to −35 Nm; P < 0.001) between Pre and Post without reductions in voluntary activation ( P = 0.72); there were no differences between conditions (MVC: P = 0.75, twitch: P = 0.55). There were no differences in tissue saturation index ( P = 0.27), deoxyhemoglobin concentrations ( P = 0.86) or sEMG activity ( P = 0.92) throughout the AOT. These findings demonstrate that IPC does not preserve neural drive during an all‐out 3 min isokinetic leg extension task. Abstract : This study aimed to investigate how ischemic preconditioning (IPC)‐enhanced muscle oxygenation influences reductions in neural drive induced by a maximal dynamic exercise test. Our results show that pre‐post declines in neural drive were unaffected by IPC and furthermore, neither surface electromyography nor measures of skeletal muscle oxygenation were influenced by IPC throughout the exercise test.